1999
DOI: 10.1523/jneurosci.19-10-04110.1999
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Locomotor Activity and Conditioned Reward to Cocaine by Brain-Derived Neurotrophic Factor

Abstract: The mesolimbic dopamine (DA) system has been implicated in drug reward, locomotor sensitization, and responding for reward-related stimuli [termed conditioned reinforcers (CR)]. Here, we investigated the effect of brain-derived neurotrophic factor (BDNF), which enhances the survival and function of dopaminergic neurons, on stimulant-induced locomotor sensitization and responding for CR. In experiment 1, BDNF was infused into the nucleus accumbens (NAc) or ventral tegmental area over 2 weeks via chronically imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
278
2
6

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(299 citation statements)
references
References 71 publications
13
278
2
6
Order By: Relevance
“…Of particular interest is the observation that PCP, or its congener MK-801, modulates the cAMP response element-binding protein (CREB) transcription factor family and the brain-derived neurotrophic factor (BDNF) (CastrĂ©n et al, 1993;Hughes et al, 1993;Storvik et al, 2000). CREB and BDNF have been studied for their transient and long-lasting, respectively, roles in the reinforcing effects of drugs (Horger et al, 1999;Nestler, 2001). Moreover, it has been recently revealed that within the mesolimbic dopaminergic system, activation of CREB is associated with the dysphoric effect of early cocaine withdrawal (Pliakas et al, 2001) and BDNF induces depression-like effects (Nestler et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is the observation that PCP, or its congener MK-801, modulates the cAMP response element-binding protein (CREB) transcription factor family and the brain-derived neurotrophic factor (BDNF) (CastrĂ©n et al, 1993;Hughes et al, 1993;Storvik et al, 2000). CREB and BDNF have been studied for their transient and long-lasting, respectively, roles in the reinforcing effects of drugs (Horger et al, 1999;Nestler, 2001). Moreover, it has been recently revealed that within the mesolimbic dopaminergic system, activation of CREB is associated with the dysphoric effect of early cocaine withdrawal (Pliakas et al, 2001) and BDNF induces depression-like effects (Nestler et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…General methods were according to published procedures (Horger et al, 1999) and were performed in accordance with international guidelines for the ethical use of laboratory animals and the National Institutes of Health Guide for the Care and Use of Laboratory Animals. All efforts were made to minimize animal suffering and the number of animals used.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, early phases of instrumental learning (Hernandez et al 2006;Kelly and Deadwyler 2003) elicit widespread zif/268 and arc induction throughout an extensive corticostriatal network in rats, whereas manipulation of BDNF levels in the brain alters cocaine-seeking in a regionally selective manner (Horger et al 1999;Lu et al 2004;Berglind et al 2007;Graham et al 2007). …”
Section: Functional Significance Of Gene Expression Changesmentioning
confidence: 99%
“…Furthermore, manipulation of BDNF levels in the brain alters cocaine seeking (Horger et al 1999;Lu et al 2004;Berglind et al 2007;Graham et al 2007). Additionally, early phases of instrumental learning (Hernandez et al 2006;Kelly and Deadwyler 2003) elicit widespread zif/268 and arc induction throughout an extensive corticostriatal network in rats.…”
mentioning
confidence: 99%